In-vitro Germination Studies on Hildegardia populifolia (Roxb.) Schott. & Endl. - an Endangered Tree Taxon - Anuradha, T.; Pullaiah, T. (Indian Forester, 2004)
The influential role of different factors such as acid scarification, media type, photoperiod, pH and additives on seed germination was investigated. The percentage of seed germination could be increased from 0-2 to 14-16% by subjecting the dry seeds to 30 minute scarification trcatment with conc. H2SO4. There seems to be a correlation between seed weight and germination percentage. The germination was better in half strength MS medium supplemented with GA3 (O.5mg/l). Seeds collected one month before harvesting time and cultured on half strength MS medium with GA, showed 90% germination. However they failed to grow beyond two leaf stage.